Microtubule cytoskeleton-disrupting activity of MWCNTs: applications in cancer treatment - Hevia, Lorena García (J Nanobiotechnology, 2020)
Microtubules and carbon nanotubes (CNTs), and more particularly multi-walled CNTs (MWCNTs), share many mechanical and morphological similarities that prompt their association into biosynthetic tubulin filaments both, in vitro and in vivo. Unlike CNTs, microtubules are highly dynamic protein polymers that, upon interaction with these nanomaterials, display enhanced stability that has critical consequences at the cellular level. Among others, CNTs prompt ectopic (acentrosomal) microtubule nucleation and the disassembly of the centrosome, causing a dramatic cytoskeletal reorganization. These changes in the microtubule pattern trigger the generation of ineffective biomechanical forces that result in migration defects, and ultimately in spindle-assembly checkpoint (SAC) blockage and apoptosis. In this review, we describe the molecular mechanism involved in the intrinsic interference of CNTs with the microtubule dynamics and illustrate the consequences of this effect on cell biomechanics. We also discuss the potential application of these synthetic microtubule-stabilizing agents as synergetic agents to boost the effect of classical chemotherapy that includes spindle poisons (i.e. paclitaxel) or DNA interfering agents (5-fluorouracil)-, and list some of the advantages of the use of MWCNTs as adjuvant agents in preventing cell resistance to chemotherapy. [Image: see text]